Mandatory vs. optional split-dose bowel preparation for morning colonoscopies: a pragmatic noninferiority randomized controlled trial - Dolovich, Casandra; Unruh, Claire; Moffatt, Dana C.; Loewen, Carrie; Kaita, Brennan; Barkun, Alan N.; Martel, Myriam; Singh, Harminder (Endoscopy, 2023)
Background We compared the effectiveness of optional split-dose bowel preparation (SDBP) with mandatory SDBP for morning colonoscopies in usual clinical practice.Methods Adult patients undergoing outpatient early morning (8:00 AM–10:30 PM) and late morning (10:30 AM–12:00 PM) colonoscopies were included. Written bowel preparation instructions were provided based on randomization: one group were instructed to take their bowel preparation (4 L polyethylene glycol solution) as a split dose (mandatory), while the comparator group was allowed the choice of SDBP or single-dose bowel preparation administered entirely on the day before (optional). The primary end point, using noninferiority hypothesis testing with a 5 % margin, was adequate bowel cleanliness measured by the Boston Bowel Preparation Scale (BBPS) and defined by a BBPS score ≥ 6.Results Among 770 randomized patients with complete data, there were 267 mandatory SDBP and 265 optional SDBP patients for early morning colonoscopies, and 120 mandatory SDBP and 118 optional SDBP patients for late morning colonoscopies. Optional SDBP was inferior to mandatory SDBP, with a lower proportion of adequate BBPS cleanliness for early morning colonoscopies (78.9 % vs. 89.9 %; absolute risk difference [aRD] 11.0 %, 95 %CI 5.9 % to 16.1 %), but was not statistically different for late morning colonoscopies (76.3 % vs. 83.3 %; aRD 7.1 %, 95 %CI −1.5 % to 15.5 %).Conclusions Optional SDBP is inferior to mandatory SDBP in providing adequate bowel preparation quality for early morning colonoscopies (8:00 AM–10:30 AM), and probably inferior for late morning colonoscopies (10:30 AM–12:00 PM).